Penguatan Kapasitas dan Peran Tenaga Kesehatan Berbasis Komunitas dalam Implementasi G1R1J di Puskesmas Kota Ende - Kopong, Pius; Krispina Owa; Syaputra Artama (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant public health issue in Indonesia, including in the working area of Puskesmas Kota Ende, which has reported high case numbers over the past five years. The national strategy